2011
DOI: 10.1007/s10334-011-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood longitudinal (T 1) and transverse (T 2) relaxation time constants at 11.7 Tesla

Abstract: Object The goal of the study was to determine blood T1 and T2 values as functions of oxygen saturation (Y), temperature (Temp) and hematocrit (Hct) at an ultrahigh MR field (11.7 T) and explore their impacts on physiological measurements, including cerebral blood flow (CBF), blood volume (CBV) and oxygenation determination. Materials and methods T1 and T2 were simultaneously measured. Temperature was adjusted from 25 to 40°C to determine Temp dependence; Hct of 0.17–0.51 to evaluate Hct dependence at 25 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
6
31
0
Order By: Relevance
“…Also, T1 values of human blood in the present study were linearly dependent on B 0 , which is consistent with previous studies [15][16][17][18] (Fig. 4).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Also, T1 values of human blood in the present study were linearly dependent on B 0 , which is consistent with previous studies [15][16][17][18] (Fig. 4).…”
supporting
confidence: 82%
“…T1 values of blood may be influenced by Hct, temperature, pH, and oxygenation levels. 9,[15][16][17][18][19] In fact, accurate measurements of human blood T1 values are an important topic in itself because these values are an important MR parameter for quantitative physiological and functional MR measurements, such as arterial spin labeling with cerebral blood volume calculations. Previously, T1 values of bovine blood had been measured at 1.5 T, 3 T, 18 4.7 T, 7 T, and 9.4 T. 17 T1 values of rat blood have also been measured at 11.7 T. 16 Human blood T1 values have also recently been measured at 3 T 19 and 7 T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transverse relaxation time of the white and grey matter at 3T is assumed to be 80 ms [7], while the transverse relaxation time in tumour tissue may be longer (up to 200 ms). The transverse relaxation time of blood at 3T depends on the oxygenation level, and is in the range of 80-120 ms [8,9], considering that the blood water T2 value was reported to be approximately 127 and 163 ms at 1.5 T for an oxygen fraction of 0.6 and 0.7, respectively [10], and the T2 also decreases with increasing B 0 [11]. Finally, the transverse relaxation time of CSF should be much longer, and relevant CSF partial volume would increase the T2 fast value.…”
Section: Post-processing Of Dw-mr Imagingmentioning
confidence: 95%
“…It is however difficult to extrapolate whether these components are mainly unilateral or bilateral; most of the studies in rats clearly showed the presence of a bilateral cortical connectivity in several cortical regions (mainly visual, somatosensory, auditory, and motor) also under isoflurane (Liang et al, 2012;Zhou et al, 2014); nevertheless, not all studies in mice using isoflurane as anesthetic found the same degree of bilateral connectivity (Jonckers et al, 2011;Guilfoyle et al, 2013), whereas a more prominent interhemispheric connectivity has been found using other anesthetics (Nasrallah et al, 2014;Sforazzini et al, 2014). In this study, we detected significant interhemispheric direct connectivity (with partial correlation analysis) in hippocampal, motor, auditory, visual, and piriform cortices, and intrahemispheric connectivity between somatosensory, motor, and auditory cortices.…”
Section: Fc In the Aging Mouse Brainmentioning
confidence: 99%